Reduced striatal activation during reward anticipation due to appetite-provoking cues in chronic schizophrenia: a fMRI study - Grimm, Oliver; Vollstädt-Klein, Sabine; Krebs, Lena Theresa; Zink, Mathias (Schizophrenia research, 2012)
The occurrence of weight gain in schizophrenia (SZ) has profound clinical impact and interacts with antipsychotic medication, life style and disease severity. The functional neuroanatomy underlying altered nutritional behavior is unraveled, but dysregulated reward anticipation might be one of the involved neuronal mechanisms. The striatum, a core region of the reward network and salience attribution, was previously shown to regulate appetite perception and eating behavior. We studied patients suffering from chronic schizophrenia with a stable medication in comparison to age and gender matched healthy adults. Every subject had to undergo a 6h fasting period before a newly developed, appetite-provoking fMRI task was applied. Subjects saw visual stimuli of appetitive food items in a 3Tesla scanner. In healthy controls food images elicited stronger activation in the striatum compared to SZ patients. When adjusting a ROI-based striatal activation for medication and weight, the group difference remained still significant. This points an effect of illness independent of antipsychotic medication. These data underscore the involvement of the striatum into salience attribution, reward anticipation and the neuronal pathways leading to altered eating behavior and weight gain in schizophrenia.
Gesehen am 24.05.2018